Nature's beauty secrets : recipes for beauty treatments from the world's best spas - Gallagher, Dawn (Universe, 2011)
Presents recipes for beauty treatments for the face and body which use natural oils, fruits, and other kitchen ingredients, along with descriptions of the treatments available at spas located around the world --